Childhood and the Law / Childhood and the Law in Canada: The Family/State Relationship by Patrick Joseph Ryan - Chambers, Lori (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2025)
Childhood and the Law in Canada: The Family/State Relationship provides comprehensive case reviews of six leading Canadian decisions regarding the relationships among children, their parents, and the state. Each chapter provides the facts of the case, places these facts in historical context, and closes with a discussion of the social implications of the law, subsequent statutory reform, and ongoing public debates. The book is intended for use in courses on childhood and the law in the Canadian context and provides exceptionally complete materials for briefing and/or mooting the cases presented. It will be welcomed by instructors, researchers, students, and a wider audience of those interested in children’s legal rights and status.